Deadlock-free Scheduling of Flexible Manufacturing Systems Subject to No-Wait Constraints - Yin, Pei; Luo, JianChao (International Conference on Control, Automation and Robotics : proceedings, 2023)
The scheduling problem of deadlock-prone flexible manufacturing systems (FMSs) subject to no-wait constraints is widespread in industrial production. Intricate constraints make it challenging to search optimal solutions with criteria of minimal makespan. The quality of a heuristic function largely determines the performance and efficiency of a heuristic search algorithm. Based on a place-timed Petri net (PN) model, a novel heuristic function is developed and used in the A-star (A^{*}) algorithm. Since it considers the deadlock-free and no-wait constraints, it owns stronger ability in choosing promising vertexes. Computational results demonstrate its superiority over the state-of-the art ones.